L’Alliance Mutuelle, face au changement - Mondoux, Léon (Assurances, 1984)
Life insurance has been faced with certain problems in the last few years, and insurers have tried to adapt by changing their management policies. Mr. Léon Mondoux describes how the Alliance Mutuelle has reacted to the new conditions. His article is of great interest as he describes in detail new directions and steps taken.